Dampak Modal, Biaya Produksi, Dan Tenaga Kerja Terhadap Pendapatan UMKM Bidang Manufaktur Di Kota Bandar Lampung - Grace Sani Br. Siahaan; Irawan Irawan; Endah Yuni Puspita Sari (Jurnal Riset Akuntansi, 2024)
This study aims to analyze the influence of capital, production costs, and labor on the income of MSMEs in the manufacturing sector in Bandar Lampung City. This study uses a purposive sampling method involving 100 respondents whose data collection was carried out by distributing questionnaires to MSME actors in the sector. Data analysis was carried out using SMART PLS software version 3. The results of the study indicate that: (1) capital has a significant influence on the income of MSMEs in the manufacturing sector in Bandar Lampung City, (2) production costs also have a significant influence on the income of MSMEs in the region, and (3) labor is proven to have a significant influence on the income of MSMEs in the manufacturing sector in Bandar Lampung City.